Four-Step Domino Reaction Enables Fully Controlled Non-Statistical Synthesis of Hexaarylbenzene with Six Different Aryl Groups** - Grau, Benedikt; Dill, Maximilian; Hampel, Frank; Kahnt, Axel; Jux, Norbert; Tsogoeva, Svetlana (Angewandte Chemie International Edition, 2021)
Hexaarylbenzene (HAB) derivatives are versatile aromatic systems playing a significant role as chromophores, liquid crystalline materials, molecular receptors, molecular-scale devices, organic light-emitting diodes and candidates for organic electronics. Statistical synthesis of simple symmetrical HABs is known via cyclotrimerization or Diels-Alder reactions. By contrast, the synthesis of more complex, asymmetrical systems, and without involvement of statistical steps, remains an unsolved problem. Here we present a generally applicable synthetic strategy to access asymmetrical HAB via an atom-economical and high-yielding metal-free four-step domino reaction using nitrostyrenes and alpha,alpha-dicyanoolefins as easily available starting materials. Resulting domino product-functionalized triarylbenzene (TAB)-can be used as a key starting compound to furnish asymmetrically substituted hexaarylbenzenes in high overall yield and without involvement of statistical steps. This straightforward domino process represents a distinct approach to create diverse and still unexplored HAB scaffolds, containing six different aromatic rings around central benzene core.
CRIS-Team WoS Importer:2021-09-03